The effect of competitive prices and service quality on decisions to use Grab bike transportation services: Case study of Borneo University Tarakan students - Nursiah Sabdin; Suryaningsih; Erick Karunia; Faerozh Madli; Ang Hong Loong (Faculty of Economics and Business, Mulawarman University, 2025)
The influence of competitive pricing and service quality on the decision to use Grab Bike transportation services is an important aspect of consumer behavior and business strategy. Research shows that competitive pricing influences users' choices, with them tending to choose the economical option. On the other hand, service quality, such as safety and convenience, affects users' perception of the user experience. The balance between competitive pricing and good service quality plays a key role in determining whether users will continue to use Grab Bike services. The population in this study were all students of the University of Borneo Tarakan the data analysis technique in this study used multiple regression analysis to determine the effect of variable Competitive prices and service quality on decisions to use grab bike transportation services.